Begin by writing it down:-5a + 6 = 56Subtract 6 from each side:-5a = 50Divide each side by 5:-a = 10Multiply each side by -1 :a = -10
13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2
Whan a = 2 and b = 6, 5a + 2b = 5*2 + 2*6 = 10 + 12 = 22
5 x 6 = 30, 30 + 8 =...
20 + 6 - 56 = -30
Begin by writing it down:-5a + 6 = 56Subtract 6 from each side:-5a = 50Divide each side by 5:-a = 10Multiply each side by -1 :a = -10
The statement is false. 5a +6 = 5a + 30 Subtract 5a from both sides: 6 = 30 and that is plain and simple rubbish!
13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2
Whan a = 2 and b = 6, 5a + 2b = 5*2 + 2*6 = 10 + 12 = 22
5 x 6 = 30, 30 + 8 =...
20 + 6 - 56 = -30
6a + 4 = 5a - 2 means that 6a - 5a = -2 - 4 which gives a = -6
3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)
Yes.
g=6
The value of a in the equation 5a plus 2a = 6-6a is a=6/11.
12a + 6b + 6c = 6(2a + b + c)